Perceived HIV stigmatization, HIV/AIDS cognition and personality as correlates of HIV self-disclosure among people living with HIV in Ibadan, Nigeria (2011)
The relationship between perceived HIV stigmatization, HIV/AIDS cognition, personality and HIV self-disclosure (HSD) was investigated. The influence of age and gender on these was also examined PLWHA (N421) in Ibadan, Nigeria participated in the cross-sectional study. A positive relationship of extraversion (r=-. 738, df=421, P<.05), HIV cognition (r=-.621, df=421, P<.05), neuroticism (r=-.212, df=421, P<.05) and agreeableness personality traits (r=-.155,df= 421, P<,05) with HSD was observed. A 2x2x2x2 factorial analysis showed that old females, with low perceived stigmatisation, but with good HIV cognition (n=23, Ẋ =18.2, SD=3.8) were most likely to disclose their status. Perceived stigmatisation, HIV cognition, and personality jointly predicted HSD (R2=.52; F (3,418) =.7.66 P <.05). Negative HIV cognition, perceived stigmatization, openness and conscientious personality traits are major barriers to HSD. Non disclosure remains an enormous barrier to the fight against HIV and AIDS. Policies and actions should therefore focus on these issues in HIV prevention, care and support.